Alterations in reversible protein histidine phosphorylation as intracellular signals in cardiovascular disease - Wieland, Thomas; Attwood, Paul V. (Frontiers in Pharmacology, 2015)
Reversible phosphorylation of amino acid side chains in proteins is a frequently used mechanism in cellular signal transduction and alterations of such phosphorylation patterns are very common in cardiovascular diseases. They reflect changes in the activities of the protein kinases and phosphatases involving signaling pathways. Phosphorylation of serine, threonine and tyrosine residues has been extensively investigated in vertebrates, whereas reversible histidine phosphorylation, a well-known regulatory signal in lower organisms, has been largely neglected as it has been generally assumed that histidine phosphorylation is of minor importance in vertebrates. More recently, it has become evident that the nucleoside diphosphate kinase isoform B (NDPK B), an ubiquitously expressed enzyme involved in nucleotide metabolism, and a highly specific phosphohistidine phosphatase (PHP) form a regulatory histidine protein kinase /phosphatase system in mammals. At least three well defined substrates of NDPK B are known, the β subunit of heterotrimeric G proteins (Gβ), the intermediate conductance potassium channel SK4 and the Ca2+ conducting TRP channel family member, TRPV5 have been identified. In each of these proteins the phosphorylation of a specific histidine residue regulates cellular signal transduction or channel activity. This article will therefore summarize our current knowledge on protein histidine phosphorylation and highlight its relevance for cardiovascular physiology and pathophysiology.